KETERAMPILAN DASAR MENGAJAR DAN PENGUASAAN KOMPETENSI GURU (Suatu Proses Pembelajaran Micro) - Mansyur Mansyur (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2017)
Micro teaching can be meant training way of skill education or teaching practice in limited scope and a small studying model which is called real taching. Thus micro teaching can provide a teacher or aspirant teacher the base various skill of teaching, and as exercise tool to practice teaching base skill. Micro teaching process can implementate the teaching base skill in exercise type in front of friends (peer teaching) dan the next step teaching namely teaching in front of real students (real teaching). In Exercise micro teaching, aspirant teacher can be trainned to practice some teories of eight teaching base skill. Micro Teaching process can also implementate four. teacher’s competences (pedagogy, professional, personality and social) in teaching studying process